Aquatic Fate and Ecotoxicology Effect of ZnS:Mn Quantum Dots on Chlorella vulgaris in Fresh Water - Bingbing Deng; Rania Maaloul; Sophie Nowak; Yann Sivry; Claude Yéprémian; Souad Ammar; Fayna Mammeri; Roberta Brayner (MDPI AG, 2024)
With the increasing integration of nanomaterials into daily life, the potential ecotoxicological impacts of nanoparticles (NPs) have attracted increased attention from the scientific community. This study assessed the ecotoxicity of ZnS quantum dots (QDs) doped with varying molar concentrations of Mn2+ on Chlorella vulgaris. The ZnS:Mn QDs were synthesized using the polyol method. The size of the ZnS:Mn QDs ranged from approximately 1.1 nm to 2 nm, while the aggregation size in Seine River water was 341 nm at pH 6 and 8. The presence of ZnS:Mn (10%) NPs exhibited profound toxicity to Chlorella vulgaris, with immediate reductions in viability (survival cells) from 71%, 60% to 51%, 52% in BG11 and Seine River water, respectively, at a concentration of 100 mg L−1 of ZnS:Mn (10%) NPs. Additionally, the ATP content in Chlorella vulgaris significantly decreased in Seine River water (by 20%) after 3 h of exposure to ZnS:Mn (10%) NPs. Concurrently, SOD activity significantly increased in Seine River water, indicating that the ZnS:Mn (10%) NPs induced ROS production and triggered an oxidative stress response in microalgae cells.